2021
DOI: 10.1186/s12992-021-00744-x
|View full text |Cite
|
Sign up to set email alerts
|

The Health Impact Fund: making the case for engagement with pharmaceutical laboratories in Brazil, Russia, India, and China

Abstract: Despite progress in global health, the general disease burden still disproportionately falls on low- and middle-income countries. The health needs of these countries’ populations are unmet because there is a shortage in drug research and development, as well as a lack of access to essential drugs. This health disparity is especially problematic for diseases associated with poverty, namely neglected tropical diseases and microbial infections. Currently, the pharmaceutical landscape focuses on innovations determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This initiative is critical in the drug development process, regenerative medicine, and organ engineering. This technology can facilitate the development of precision bills and medical formulations that depend on age and physiology ( 51 ). With these bio-printers, innovations in tissue engineering, bio-inks, and microfluidics can be scaled up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This initiative is critical in the drug development process, regenerative medicine, and organ engineering. This technology can facilitate the development of precision bills and medical formulations that depend on age and physiology ( 51 ). With these bio-printers, innovations in tissue engineering, bio-inks, and microfluidics can be scaled up.…”
Section: Discussionmentioning
confidence: 99%
“…These technologies are capable of making tissues have the desired structure and feature with a good cell survival rate, which was a major limitation in previous techniques used in testing new pharmaceutical products (50). Through electro-hydrodynamic printing techniques, new 3D bioprinters help deliver higher cell survival rates and tissues with micro and nano-scale features (12,(51)(52)(53)(54)(55)(56). Thus, through pharmaceutical innovation, the BRICS countries have asserted their autonomy, boosting the quest for self-sufficiency (55).…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…Research by Lee points out that low -and middle-income countries continue to face unequal disease burdens, including a lack of drug R&D and poor access to essential medicines. The Health Impact Fund proposes collaborative solutions that will consider working with pharmaceutical companies in Brazil, Russia, India, and China to expand reach, spur local innovation, and promote a more equitable path to drug discovery [7]. Li analyzed the delays in drug development in China from the start of clinical trials to the regulatory process and identified critical underlying factors.…”
Section: Related Researchmentioning
confidence: 99%